Effect of Soil Organic Matter Content and pH on Toxicity of Cadmium to Paronychiurus kimi (Lee) (Collembola) - Son, Jino; Mo, Hyoung-ho; Kim, Jhi-hong; Ryoo, Mun Il; Cho, Kijong (Journal of Asia-Pacific entomology, 2007)
The heterogeneous physico-chemical properties of soil make it difficult to normalize the toxicological effects of metals in the Collembolan species Paronychiurus kimi (Lee). Furthermore, the physico-chemical properties of soil themselves can function as limiting factors that affect population fitness. In this study, the effects of soil organic matter (OM) and pH on the biological performance of P. kimi were assessed, and the influence of these properties on cadmium toxicity to P. kimi was also assessed at the individual and population levels. The OM and pH were found to significantly influence offspring production. All toxicological values of cadmium to P. kimi showed consistent patterns of increase with increasing OM and pH values, implying a decreased toxicity. The 28-d LC 50 values varied from 34.9 to 115.9 mg/kg, and the 28-d EC 50 and 28-d r i =0 also varied depending on the OM and pH values. These findings indicate that the OM and pH values themselves are important factors in determining not only the biological performance of P. kimi but also the toxicity of cadmium to P. kimi on the individual and population levels. Therefore, when ecological risk assessments are conducted for a certain soil, pre-examinations of the effects of abiotic factors and the selection of an appropriate endpoint must be accomplished before establishing levels of chemicals of concern (COC) for a certain species.